Unpacking the green entrepreneurial orientation–sustainable performance nexus: A conceptual framework for SRDI SMEs in China - He, Yuling; Tee, Poh Kiong (International Journal of Innovative Research and Scientific Studies, 2026)
Amid escalating global environmental challenges and China’s "dual carbon" strategic goals, the green transformation of small and medium-sized enterprises (SMEs), particularly “specialized, refined, distinctive, and innovative” (SRDI) firms, has become a critical pathway to achieving high-quality economic development and ecological sustainability. Drawing on the resource-based view, dynamic capabilities theory, and contingency theory, this study develops an integrated conceptual framework to examine the mechanisms and boundary conditions through which green entrepreneurial orientation (GEO) influences sustainable performance in SMEs. Specifically, green innovation (GI) and green supply chain management (GSCM) are conceptualized as parallel mediating variables, while green technology dynamism (GTD) is introduced as a moderating variable. Based on a systematic review of the literature, this study proposes that GEO enhances sustainable performance through two complementary pathways GI and GSCM, while GTD significantly moderates the strength of these indirect effects, thereby forming a moderated mediation mechanism. By integrating multiple theoretical perspectives, this study provides a parsimonious and systematic explanation of the underlying mechanisms and boundary conditions linking green technology dynamism to sustainable performance. The findings not only enrich the literature on green transformation but also offer important implications for SMEs in formulating and implementing green strategies, as well as for policymakers in designing targeted policies to facilitate enterprise-level sustainability transitions.